2019
DOI: 10.1016/j.yclnex.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Diet from Mantisa religiosa-egg case abolishes pulmonary dysfunctions triggered by sub-acute exposure to aerosolized-petroleum hydrocarbons in rat model

Abstract: action by which 4% DSMREC prevents petroleum-induced pulmonary toxicity in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 57 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…Also, some essential trace elements were determined which include calcium (10,800 mg/kg), potassium (5,600 mg/kg), magnesium (200 mg/kg), iron (165.48 mg/kg), sodium (116.29 mg/kg), manganese (57.98 mg/kg), zinc (10.69 mg/kg), and copper (3.89 mg/kg). The protein content of PMECP from our previous study revealed (69.65%) followed by carbohydrate (12.81%), fat (12.50%), and nitrogen (12.32%) (Akintunde et al., 2019).…”
Section: Methodsmentioning
confidence: 75%
See 4 more Smart Citations
“…Also, some essential trace elements were determined which include calcium (10,800 mg/kg), potassium (5,600 mg/kg), magnesium (200 mg/kg), iron (165.48 mg/kg), sodium (116.29 mg/kg), manganese (57.98 mg/kg), zinc (10.69 mg/kg), and copper (3.89 mg/kg). The protein content of PMECP from our previous study revealed (69.65%) followed by carbohydrate (12.81%), fat (12.50%), and nitrogen (12.32%) (Akintunde et al., 2019).…”
Section: Methodsmentioning
confidence: 75%
“…This suggests that production of free radicals and lipid peroxidation that were involved in the pathogenesis of some chronic diseases of both man and animals (Zheleva‐Dimitrova, Nedialkov, & Kitanov, 2010) could be prevented by foods containing high level of proteins (Kuyooro, Akintunde, Okekearu, & Maduagwu, 2019). Our previous report demonstrated that PMECP containing high quantity of proteins and phenols could be antihepatotoxic and lung protective (Akintunde et al., 2019) in animal model. However, it pertinent to say that PMECP in this study can be used as antioxidant agent against myriad of free radicals and lipid peroxidation in mammals (Akintunde et al., 2019) and fishes.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations